الأسباب المؤدية إلى وجود مشاعر سلبية تجاه الإلو عند المراىقين المسلمين ومظاىرىا والحلول المقترحة لها = Driving factors for having the feeling of resentment towards God among Muslim adolescents: its phenomena and solutions - Mohamed Ibrahim, Nada Abdelrahman; Ahmad, Masitoh (IIUM Press, 2022)
The article aims to study the causes that lead to the development of Misotheism (a sense of resentment or embitterment towards God or theistic belief in general) among Muslim adolescents. Previous studies have tackled the issue from its atheist phenomenon without investigating its causes. Therefore, the study focuses on the phenomenon of resentment and embitterment towards God, its driving factors in initial stages and its evolution into atheism among Muslim teenagers. The research highlights the importance of defending against malicious attempts from the critics of Islam who are engaged in efforts that result in severe harm to the psychology of Muslim youth everywhere. The study uses qualitative methods in which library research, method of analysis and observation are applied. The finding shows that there are three main factors that lead to this phenomenon; namely: psychological, social and cognitive causes. The psychological causes for the rebellious behavior among youth are mainly due to family breakdown. As for the social causes, they are owing to the rigidity of customs and traditions in the name of religion, Islamophobia, social injustice, and the excessive veneration of people and promotion of narcissistic behavior, while the cognitive reasons are embedded in the problem of life challenges, addictions, and social evils. The study also proposes some practical solutions for the issues discussed.